Analisis Pengaruh Distribusi Produk Domestik Regional Bruto dan Laju Pertumbuhan PDB per Tenaga Kerja terhadap Indeks Pembangunan Manusia di Indonesia - Syarifah Sri Rohayaa; Devi Andriyani (LPPM Universitas Malikussaleh – Indonesia, 2022)
The purpose of this study was to analyse theeffect of the distribution of GRDP and the growth rate of GDP per labor on thehuman development index in Indonesia by using panel data analysis. The scope of this research covers 10 provinces in Indonesia over period of 10 years (2011-2020) obtained from the Central Statistics Agency. The regression tool in this study uses eviews 9. The result show that the variable GDP distribution has a significant effect on the human development index, the variable GDP growth rate per labor has no significant effect on the human development index in Indonesia. And the highest intercept result in the 10 Provinces that have been analysed is DI Jogjakarta Province with an intercept 75,16%.